Labor Productivity Growth and Its Contribution to the GRDP of Thai Nguyen Province, Vietnam - Nguyen Dac Dung; Tran Quang Huy (Randwick International of Social Science Journal, 2024)
This research focuses on analyzing the trajectory of labor productivity growth and its consequential impact on Thai Nguyen Province's Gross Regional Domestic Product (GRDP) between 2017 and 2022. By employing statistical methodologies and descriptive statistics sourced from the Statistical Office of Thai Nguyen Province, this study illuminates the dynamic nature of labor productivity within the province. Over this period, there was a consistent fluctuation in productivity levels, reflecting an overall upward trend. Notably, the average productivity growth rate stood at a substantial 12.61%, showcasing the province's evolving economic landscape. Remarkably, 2021 emerged as the year with the most significant productivity surge, juxtaposed against the comparatively sluggish growth witnessed in 2020. Additionally, this investigation firmly establishes labor productivity as a predominant driver of GRDP growth in Thai Nguyen Province, surpassing the influence exerted by capital and labor inputs. These findings underscore the paramount importance of labor productivity as the linchpin of economic progress within the province, signifying its pivotal role in shaping the region's economic trajectory compared to other contributing factors.